L’échec de la réforme de la politique d’immigration de l’administration Bush - Laurence Gervais (Revue LISA)
For more than 20 years now, successive American administrations have tried to find a solution to the problem of illegal immigration to the United States. From the deportation of all illegal immigrants to their legalization, from taking immigrants off the welfare rolls to increasing their eligibility for aid, every solution seems to have been proposed and examined. The concerns of these last 20 years recall the First Continental Congress concerned about the risks of attracting the “unwanted” and of creating a class of “dependent” people by granting land ownership to immigrants too easily. Today, it is impossible not to realize how much immigrants are part of the American economy, as consumers as well as workers. According to the 2000 Census, the number of foreign-born residents was 31.1 million out of a total of 281.4 million. Under the Bush administration, 6 million individuals were arrested and deported. Some statistics mention around 12 million illegal immigrants, 7 million of them employed in the United States. If 9.11 changed things dramatically, introducing the fear of admitting potential terrorists amongst candidates for immigration to the United States, it is the multiplicity of actors in the debate that is partly responsible for the failure of the Bush administration’s attempts at reforming American immigration policy.